STUDI LITERATUR: PENGARUH TERAPI PIJAT REFLEKSI KAKI TERHADAP KELELAHAN PADA PASIEN HEMODIALISIS - Latif Fajar Pamungkas; Fauziah Hamid Wada; Puji Astuti; Ashar Prima (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Hemodialysis can cause various kinds of problems including fatigue, around 7-92% of hemodialysis patients experience fatigue. One of the therapies that can overcome this fatigue is reflexology foot massage therapy. This literature review aims to determine the effect of foot reflexology massage on hemodialysis patients with fatigue problems. The design in this scientific paper is a literature review search using electronic data base namely ProQuest and Pubmed. The keywords used in the search are hemodialysis, foot reflexology, fatigue. inclusion criteria used in the article are accessible full text available in english and indonesian years the articles used are limited to the last ten years, results are found each of 2 articles from google schoolar and pubmed, from the four articles discussing the effectiveness of foot reflexology massage on the decline fatigue in hemodialysis patients. The results of the study showed the benefits of foot reflexology in reducing fatigue in hemodialysis patients